Multivariate t distributions and their applications - Kotz Samuel; Nadarajah Saralees (Cambridge CUP, 2004)
The first part of the book emphasizes theoretical results of a probabilistic nature. In the second part of the book, these are supplemented by a variety of statistical aspects. Various generalizations and applications are dealt with in the final chapters
Keywords: Distribution(Probability theory); Multivariate analysis